Design of Arduino UNO based smart irrigation system for real time applications - Ramasamy, Palanisamy; Pandian, Nagarajan; Mayathevar, Krishnamurthy; Ravindran, Ramkumar; Kandula, Srinivasa Rao; Devadoss, Selvabharathi; Kuppusamy, Selvakumar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
The fundamental principle of the paper is that the soil moisture sensor obtains the moisture content level of the soil sample. The water pump is automatically activated if the moisture content is insufficient, which causes water to flow into the soil. The water pump is immediately turned off when the moisture content is high enough. Smart home, smart city, smart transportation, and smart farming are just a few of the new intelligent ideas that internet of things (IoT) includes. The goal of this method is to increase productivity and decrease manual labour among farmers. In this paper, we present a system for monitoring and regulating water flow that employs a soil moisture sensor to keep track of soil moisture content as well as the land’s water level to keep track of and regulate the amount of water supplied to the plant. The device also includes an automated led lighting system.